Pengaruh Produk Domestik Regional Bruto, Upah Minimun Provinsi, dan Indeks Pembangunan Manusia Terhadap Penyerapan Tenaga Kerja di Indonesia Tahun 2016-2022 - Azzahra, Fadilah; Mukhtar, Saparuddin; Iranto, Dicky (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Labor issues are a crucial issue that has not been resolved to date. The existence of a mismatch between the needs of companies and job seekers who want to get a job according to their abilities is the main problem of employment in Indonesia. This study aims to determine the effect of Gross Regional Domestic Product, Provincial Minimum Wage, and Human Development Index on Labor absorption in Indonesia in 2016 - 2022 using secondary data and multiple linear regression analysis of panel data with quantitative methods processed using Eviews 9 software. Total The samples used were 34 provinces in Indonesia and 196 observation units. The results showed that the Gross Regional Domestic Product variable had a positive and significant effect on Labor absorption in Indonesia in 2016 – 2022, the Provincial Minimum Wage variable had a negative and significant effect on Labor absorption in Indonesia in 2016 – 2022, the Human Development Index variable had a positive and significant impact on Labor Absorption in Indonesia in 2016 – 2022.